The Kuda Kepang Mabuk Ritual Dance: Symbolic Intitiation into a Mystical Journey: (Tari Ritual Kuda Kepang Mabuk: Inisiasi Simbolik Perjalanan Mistik) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2013)
This article concerning the Kuda Kepang Mabuk (KKM) ritual dance aims to study the phenomenon of trance as a symbolic manifestation of the mystical journey of the dancers during performance. The study was carried out using a qualitative approach and applying ethnographic strategies that focus on the relationship between behaviour and culture. The concept of homo religious in which humans are incomplete at the time of their birth and must undergo initiation in order to change their religious and social status, and thus achieve an altered existence in this world, as put forth by Mircea Eliade, is applied in this study. The study found that the several levels of trance in this ritual have a strong relationship with the metaphysical world. This finding suggests that the KKM ritual dance is still significant in the context of communities that still practise it until today, due to their belief in the need for initiation, although the initiation process has been intermingled with various religious influences.Keywords: ritual, mysticism, Kuda Kepang Mabuk, trance, initiation